Life cycle of Punctaria latifolia (Chordariaceae, Phaeophyceae) from the coast of Buenos Aires Province, South America - Gauna, Maria Cecilia (2010)
The objective of this study was to describe the morphology of Punctaria latifolia individuals from the natural environment, their life cycle under culture conditions and the caryology of different phases. The life cycle of Punctaria latifolia was studied under culture conditions (140 μmol m-2 s-1; 12 h/12 h; 21 ± 1 °C). Fertile sporophytes were collected in the intertidal zone of Bahía San Blas (Buenos Aires, Argentina, South America), in August and December 2003. These macroscopic laminar plants were found adhered to the rocky substrate and on Spartina alterniflora plants. Sporophytes from the natural environment presented both plurilocular and unilocular sporangia, which released plurispores and unispores, respectively. The asexual reproduction was evidenced by the germination of unispores by formation of a single - pole germination that formed microscopic filamentous gametophytes. Terminal and intercalar gametangia released isogametes. Zygotes reconstituted the macroscopic phase. Chromosome counts gave 16 and 8 for sporophytic and gametophytic phases, respectively. This species presented a haplodiplobiontic heteromorphic life cycle as well as a direct type, when plurispores produced plethysmothalli.